2015
DOI: 10.3109/10641963.2015.1060985
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of gene polymorphisms of the renin–angiotensin–aldosterone system on essential hypertension in Kazakhs in Xinjiang

Abstract: There was a strong synergistic effect between ACE I/D and CY11B2 T-344C and a moderate effect between both ACE I/D and CY11B2 T-344C and AGT A-6G. AGT -6G, ACE D, and CY11B2 -344C increased susceptibility to EH. REN Taq I, AGT -6G, CY11B2 -344 C and ACE D were associated with male and female EH, respectively. H1 and H3 of AGT were protective and risk haplotypes, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 18 publications
1
12
1
1
Order By: Relevance
“…They observed that DD genotype frequency was higher in HT patients than controls, and II genotypes were similar in both groups (10 (29). Previous studies demonstrated that there were (13). In Turkish population, contrary to our results, Gunes et al found significant difference between AGT1R A1166C polymorphism allele frequencies and HT.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…They observed that DD genotype frequency was higher in HT patients than controls, and II genotypes were similar in both groups (10 (29). Previous studies demonstrated that there were (13). In Turkish population, contrary to our results, Gunes et al found significant difference between AGT1R A1166C polymorphism allele frequencies and HT.…”
Section: Discussioncontrasting
confidence: 99%
“…RAAS genes including ACE, AGT, and AGT1R are polymorphic genes. There are many studies investigating the relation between RAAS gene polymorphisms and the development and incidence of HT; however, conflicting results were also reported (3,10,(12)(13)(14)(15). It is possible that selection criteria of patients, environmental factors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The ACE I/I genotype confers a low risk of cerebral infarction or other cerebral vascular pathology, such as cerebral white matter changes, in patients with AD. In contrast, the ACE D/D genotype is involved in susceptibility to hypertension . Hypertension, cerebrovascular diseases and cerebral white matter changes negatively affect cognition .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the ACE D/D genotype is involved in susceptibility to hypertension. 22,23 Hypertension, cerebrovascular diseases and cerebral white matter changes negatively affect cognition. 24,25 Therefore, considering vascular pathology, the ACE I/I genotype should confer a protective effect in the clinical course of AD.…”
Section: Discussionmentioning
confidence: 99%
“…Aldosterone plays a detrimental role on the cerebrovascular and the cardiovascular system, and it increases oxidative stress, which causes endothelial dysfunction and accumulation of collagen, leading to reduced elasticity of vessel walls. 6 The aldosterone synthase gene (CYP11B2) locus is an important candidate region in the development of hypertension, 7 diabetic nephropathy, 8 type 2 diabetes mellitus, 9 and atrial fibrillation. 10 Because it has been suggested in a meta-analysis that the CYP11B2 -344T/C polymorphism was associated with ischemic stroke, 11 we suspect that this polymorphism is probably associated with the development of TIA.…”
Section: Introductionmentioning
confidence: 99%